Hepatite B oculta em subgrupo de doadores de sangue da Fundação de Hematologia e Hemoterapia do Amazonas (FHEMOAM) e em grupo de moradores do município de Eirunepé Am - Raulino, Raisa Clareana Silva (2015)
Hepatitis B is considered one of the main infectious diseases worldwide representing an important public health challenge affecting around 2 billion people, many of them with chronic infection with hepatitis B virus ( HBV). The diagnosis of HBV is based on the positivity to the surface antigen of HBV (HBsAg). However, viral persistence identified by HBV-DNA has been described in HBsAg negative individuals, defining the occult hepatitis B infection (OHB). Occult hepatitis B is almost always associated with anti-HBc and or anti- HBs positivity, as well as low-level viral replication. OHB can represent and important public health problem in endemic areas as it can be involved in HBV transmission by blood or organ transplants by assymptomatic, apparently healthy donors. Improved tests such as the implementation of NAT (nucleic acid tests) for HIV and HCV have been adopted by hemocenters worldwide, especially in highly endemic areas as the Brazilian Amazon region. This study evaluated the prevalence of OHB in subgroups of HBsAg negative donors from a reference public health blood bank in the Amazon (Fundacao de Hematologia e Hemoterapia do Amazonas/FHEMOAM) and among a group of HBsAg negative individuals that participated in a HBV prevalence study in a highly endemic municipality in the Amazonas State/Eirunepé city. Methods/Results: Among 1.494 HBsAg negative blood donors from FHEMOAM and among 288 individuals from Eirunepe HBsAg negative and anti-HBc/anti- HBs positive or negative, pools were tested for the presence of DNA-HBV by real time PCR (qRT PCR) using primers for two genomic regions (gene X and gene S). For the pools which were positive for HBV-DNA (9 in the FHEMAOM group and 25 among Eirunepe participants), individual samples were re-tested for the presence of HBV-DNA by RT-PCR. Among the subgroup of donors from FHEMOAM 1,0% (3/294) was considered DNA-HBV positive, including 2 females and 1 male, 21, 42 and 31 years old respectively. Among these 83,3 were a first time donor and 16,7 were repeat donor. The rate of OBV in participants from Eirunepe was 3,1% (9/288): six females, 3 males, ages ranging from 27 to 64. Among these 9 OHB cases from Eirunepe, 2 were anti-HBc positives, 7 were associated with anti-HBs (above 100 mUI/ml). Conclusion: This study showed low prevalence of OBV in groups of HBsAg negative donors from FHEMOAM and moderate prevalence in participants from Eirunepe/Amazonas. Despite low rates of OBV infection identified, this study indicates that transmission by OHB can occur. These results highlight the importance of more sensitive tests to detect HBV infection, such as NAT which was implemented in 2014 representing an important tool to improve transfusional safety at FHEMOAM among donors from highly endemic areas including the capital and from inland Amazonas State